Perceptions and practices of investment: China's hydropower investments in Vietnam and Myanmar. Issue 3 (3rd July 2017) - Lamb, Vanessa; Dao, Nga
ABSTRACT: China is a major investor in hydropower in mainland Southeast Asia. These investments have triggered substantial public concern, with anti-Chinese attitudes intensifying across the region. Yet, Chinese involvement varies across the region. We examine the "practices and perceptions" of Chinese hydropower investment in Vietnam and Myanmar, attending to the framing of dominant explanations of these investments. We caution against reinforcing xenophobic narratives about China, and urge scholars to consider what these narratives obscure. Our concern is that exceptionalising the role of Chinese investors overlooks foundational issues regarding local participation and environmental governance.